Wandering through the exotic battle zone; American journalists’ travel accounts of Indonesia during the Dutch-Indonesian war - Zara, Muhammad Yuanda (Wacana, Journal of the Humanities of Indonesia, 2024)
This study analyses rarely examined English-language reportage and travel accounts on Indonesia created by two American journalists, Johnny Florea (Life) and Robert Sherrod (Time), after their visits to Indonesia between late-1945 and early-1946. The study finds that the travel accounts deliver a commentary on the course of the Dutch-Indonesian war and reveal the journalists’ fascination with Indonesian society and nature as well as their sympathy with Indonesians’ struggle for independence. However, the accounts also show that, as Westerners, they are guilty of various inaccuracies, a lack of knowledge, and cultural judgements rooted in the colonial past. It contributes to a new perspective on travel writing on Indonesia: war-zone travel writing, by explaining how foreign journalists’ travel accounts to war-torn Indonesia played a role as channels for foreigners, especially Americans, to understand Indonesia as a recently born alien “Other” in the midst of the raging war and binary division of West and East.